Antimicrobial susceptibilities of mycobacteria as determined by differential light scattering and correlation with results from multiple reference laboratories. - Conville, P S (1994)
The DAWN Model B laser light scattering instrument (Wyatt Technology Corporation, Santa Barbara, Calif.) was evaluated to assess its potential to provide rapid mycobacterial antimicrobial susceptibility test results. For Mycobacterium tuberculosis there was a clear separation between susceptible and resistant results with the isolates tested, and there was excellent correlation with reference laboratory results. For Mycobacterium avium there was no obvious breakpoint between susceptible and resistant results with the isolates tested, and correlation with reference laboratory results was less good than for M. tuberculosis. However, for M. avium there was also less agreement among reference laboratory results than for M. tuberculosis. Significant instrument design and software program changes would be required for the instrument to become a useful tool for mycobacterial susceptibility testing in the diagnostic laboratory.